(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
This paper tries to investigate the effect of blending animal bone ash (ABA) and metakaolin (MK) on the mortar compressive strength of ternary cement blends. The mortar strengths of the ternary cement blends are influenced by several parameters such as blending ratio, replacement level and curing age. The mortar strength of the ternary cement blend was optimized via response surface methodology using central composite design and Box and Behnken design. Both models were compared to obtain the best strength prediction. Results showed that both models experimental data for the prediction of the mortar strength satisfied second order polynomial regression. The mortar strength of ABA-MK-PLC experienced an increase as the blending ratio between 0.2 -0.5 and curing age between 3 -60 days whereas a slight reduction in the mortar strength was observed as the replacement level was increased between 7.5 – 12.5 wt.%. This slight diminution observed despite the high replacement level further proves that pozzolanic activities occurred. The analysis of variance (ANOVA) indicated that the curing age significantly affected the response for both CCD and BBD models respectively with the best mortar strength prediction via CCD. The ANOVA revealed that predicted R2 (R2pred) and R2 for CCD was very close in comparison with BBD and thus most suitable to describe the mortar compressive strength of the cement blends with R2pred of 0.9107. The interactive effect of the blending ratio, replacement level and curing age were also investigated and optimized. The optimum condition for the prediction of the mortar strength of the ternary cement blend were blending ratio 0.423, replacement level 7.565 wt.%, and curing age 60 days.